2022
DOI: 10.3390/children9010051
|View full text |Cite
|
Sign up to set email alerts
|

Role of Spanish Toddlers’ Education and Care Institutions in Achieving Physical Activity Recommendations in the COVID-19 Era: A Cross-Sectional Study

Abstract: To our knowledge, there are no published studies that describe the physical activity (PA) levels and objectively measure them through accelerometry in toddlers (2–3 years old) attending early childhood education and care (ECEC) institutions during the COVID-19 pandemic. The aims of this study were two-fold: (a) to analyse toddlers’ PA levels and sedentary behaviour (SB) during school hours in ECEC institutions, as well as the rate of adherence to specific recommendations on total PA (TPA) and moderate–vigorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Reducing the number of ECEC classes sharing the playground during recess time, which led to an increase in space per child from 7.4m 2 to 16.7m 2 , was associated with a 1 min reduction (− 5.1% of recess time) in time spent sedentary [65]. More children/m 2 was non-significantly associated with less time spent in sedentary in toddlers [67] and more sedentary time in preschoolers [51].…”
Section: Association Of Outdoor Play Space On Physical Activity and S...mentioning
confidence: 94%
See 1 more Smart Citation
“…Reducing the number of ECEC classes sharing the playground during recess time, which led to an increase in space per child from 7.4m 2 to 16.7m 2 , was associated with a 1 min reduction (− 5.1% of recess time) in time spent sedentary [65]. More children/m 2 was non-significantly associated with less time spent in sedentary in toddlers [67] and more sedentary time in preschoolers [51].…”
Section: Association Of Outdoor Play Space On Physical Activity and S...mentioning
confidence: 94%
“…Gubbels et al's crosssectional study compared the relative size of outdoor free play space (mean m 2 per child = 42.9 ± 45.6) for 152 children across 22 ECECs in the Netherlands [55]. Similarly, another three studies of cross-sectional design from Belgium [66] and Spain [51,67], related the average number of children per m 2 with PA of 789 children across 39 ECECs [66], 116 children across six ECECs [51], and 120 children across seven ECECs [67].…”
Section: Density Of the Outdoor Play Areamentioning
confidence: 99%
“…However, Kelly et al (2022) observed similar levels of SB and MVPA in U.S. boys and girls in daycare/preschool settings. There were different results in some other studies, of toddlers during school hours, asboys exhibited higher levels of MVPA than girls (Ellis et al, 2017;Hesketh et al, 2015;Vega-Perona et al, 2022). Also in an Australian sample, Hnatiuk et al (2012) found that young boys were more active than young girls in morning hours, while there were no sex differences over the entire day.…”
Section: Relationship Between Mean Osrac-p Pa Levels and Minutes Of T...mentioning
confidence: 67%
“…In a more recent study, Gubbels's group used accelerometry to assess PA, and age was then significantly associated with less SB and increased PA during all daytime hours (Gubbels et al, 2018). In the Spanish preschool/daycare context, Vega-Perona et al (2022) found that, during school hours, younger toddlers performed less LPA than older ones, but BMI was not associated with PA of any intensity or SB. In Swedish two-yearolds across all daytime hours, Johansson et al (2015) found that children's BMI was not significantly correlated with PA.…”
Section: Relationship Between Mean Osrac-p Pa Levels and Minutes Of T...mentioning
confidence: 99%
See 1 more Smart Citation